2020
DOI: 10.1021/acsnano.0c01511
|View full text |Cite
|
Sign up to set email alerts
|

Tough and Strong: Cross-Lamella Design Imparts Multifunctionality to Biomimetic Nacre

Abstract: The creation of structural composites with combined strength, toughness, low density, and biocompatibility remains a long-standing challenge. On the other hand, bivalve marine shells -Clinocardium exhibit strength, stiffness and toughness that surpass even that of the nacre which is the most widely mimicked model for structural composites. The superior mechanical properties of Clinocardium shells originate from their cross-lamella design, comprising CaCO3 mineral platelets arranged in an 'interlocked' herringb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 50 publications
(86 reference statements)
1
30
0
Order By: Relevance
“…by a diffusion based 68 or time-consuming gas diffusion based mineralisation. 68,96,97 The one-precursor method further was beneficial, since in our setup already minimal rinsing between the reagents prohibited the precipitation and a double diffusion method applied by Grassmann et al 98 was rather inapplicable.…”
Section: Discussionmentioning
confidence: 91%
“…by a diffusion based 68 or time-consuming gas diffusion based mineralisation. 68,96,97 The one-precursor method further was beneficial, since in our setup already minimal rinsing between the reagents prohibited the precipitation and a double diffusion method applied by Grassmann et al 98 was rather inapplicable.…”
Section: Discussionmentioning
confidence: 91%
“…The soft organic component can lead to creep, masking its effects on the elasticity. ,, A noncontact, nondeformation technique, such as Brillouin light scattering, , could extract the first-order elastic properties while elucidating the effect of both hierarchical microstructure and bio-organic constituent due to the inherent mesoscale nature of the measurement. Understanding the full mechanical properties of nacre-like structures and their response to mechanical perturbation is paramount to developing biologically inspired materials that have composite properties to withstand substantial body forces. …”
Section: Introductionmentioning
confidence: 99%
“…Using the prepared chitosan nanofibers, a new type of chitosan nanofibrous paper and scaffold materials were fabricated and characterized. In general, it is difficult for chitosan to be dissolved in water, and acetic acid was used to dissolve it for further preparation of chitosan films. Hence, we used acetic acid to dissolve the chitosan fibers and prepared a chitosan fiber acetate film (CSFAF) and scaffolds (CSFASs) as the control groups (Figure a). Both macroscopic and microscopic observations showed that the CSFAF had a flat and smooth surface (Figure A).…”
Section: Resultsmentioning
confidence: 99%